Bacterial cellulose and bacterial cellulose/polycaprolactone composite as tissue substitutes in rabbits' cornea - Rodrigo V. Sepúlveda; Fabrício L. Valente; Emily C.C. Reis; Fabiana R. Araújo; Renato B. Eleotério; Paulo V.S. Queiroz; Andréa P.B. Borges (Pesquisa Veterinária Brasileira)
ABSTRACT: In order to test the performance of bacterial cellulose/polycaprolactone composite (BC/PCL) and pure bacterial cellulose (BC) as tissue substitutes in rabbits' cornea, a superficial ulcer containing 5mm in diameter and 0.2mm deep was made in the right cornea of 36 rabbits, then a interlayer pocket was created from the basis of this ulcer. Twelve rabbits received BC/PCL membrane and 12 were treated with BC membranes, both membranes with 8mm in diameter. The remaining rabbits received no membrane constituting the control group. The animals were clinically followed up for 45 days. Three animals of each group were euthanized at three, seven, 21, and 45 days after implantation for histological examination of the cornea along with the implant. Clinical observation revealed signs of moderate inflammatory process, decreasing from day 20th in the implanted groups. Histology showed absence of epithelium on the membranes, fibroplasia close to the implants, lymph inflammatory infiltrate with giant cells, collagen disorganization, with a predominance of immature collagen fibers in both groups with implants. Although inflammatory response is acceptable, the membranes used does not satisfactorily played the role of tissue substitute for the cornea during the study period.